CD40/CD40 ligand interactions and TNFα treatment reduce activity of P105 promoter of the human papilloma virus-18 in vitro - Altenburg, A.; Abdel-Naser, M.B.; Nikolakis, G.; Wild, T.; Wojtalewicz, N. (Experimental Oncology, 2016)
Background: Cervical carcinoma cells including those infected with the oncogenic human papilloma virus (HPV) and several cervical carcinoma cell lines show a strong expression of the CD40 receptor, unlike benign cervical epithelial cells infected with HPV. The functional relevance of this up-regulated expression in the tumor is not fully understood. Nevertheless, it might offer a unique possibility to target those malignant cells due to the antiviral and antitumoral effects of the CD40/CD40 ligand (CD40L) interactions. Aim: In vitro assessment of the effect of CD40L on HPV 18-P105 promoter activity and the subsequent release of IL-6 by the promoter transfected HeLaCD₄₀ cells, which express CD40 constitutively. Material and Methods: Transfection of HeLaCD₄₀ cells was achieved by electroporation after optimizing the parameters by the pCMV-β-Gal vector and β-Gal stain. Transfected HeLaCD₄₀ cells were challenged with BHKCD40L and TNFα, in addition to BHKwt and medium alone as controls. HPV18P105 promoter activity was demonstrated by luciferase reporter gene assay while IL-6 was assessed by ELISA. Results: CD40/ CD40L interactions and TNFα treatment significantly reduced HPV18-P105 promoter activity (56.0 ± 10.2% and 64.1 ± 9.1% vs. control, respectively; p < 0.001). Likewise, IL-6, which is a sensitive cytokine of CD40 activation, was significantly increased in HeLaCD₄₀ cells in the same experiments (2.7 fold after stimulation with BHKCD₄₀L and 5.2 fold after stimulation with TNFα vs. control; p < 0.01 and p < 0.001, respectively). Conclusion: It is likely that the CD40/CD40L interactions and TNFα are effective against cervical carcinomas by repressing transcriptional activity of HPV promoter. This can result in new adjuvant treatments.